Ranking of European Union Member States Based on the Level of Knowledge Created by the Research and Development Sector - Romaniuk, Krystyna (Olsztyn Economic Journal, 2014)
The contemporary era is characterized by revolutionary changes in the economy, technological progress, social and political life. Globalization exerts pressure on businesses and entire economies to increase their competitive strength which is defined as the ability to create knowledge. Knowledge creation and management became the new management paradigms. The responsibility for knowledge creation rests mainly upon the research and development sector. The aim of this study was to rank European Union Member States based on the level of knowledge created by their respective research and development sectors and to identify knowledge creation leaders. The analysis relied on EUROSTAT data for 2007-2011 and linear ranking methods with a reference standard. Our results indicate that Western European and Scandinavian countries are the leaders in the area of knowledge creation.